2019
DOI: 10.1002/jsfa.9834
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vine water status on berry mass and berry tissue development of Cabernet franc (Vitis vinifera L.), assessed at berry level

Abstract: BACKGROUND Berry size is considered an important quality factor in red wine production. The objective of this work was to study the effect of vine water status on berry mass in field conditions, with a specific focus on berry tissue masses. RESULTS The study was carried out over 2 years in a plot located in Sicily (Italy). Two irrigation treatments were established. Dynamic evolution of berry mass and berry tissue masses at harvest were recorded. Berries produced under water deficit conditions were smaller and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…The negative correlation may be explained by a physical inhibition of the flowering process or poor phytosanitary conditions due to high precipitation. The positive correlation may also be explained by water effects on berry development after bloom (Ojeda et al, 2001;Triolo et al, 2019), especially since Vineyard C was rain-fed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative correlation may be explained by a physical inhibition of the flowering process or poor phytosanitary conditions due to high precipitation. The positive correlation may also be explained by water effects on berry development after bloom (Ojeda et al, 2001;Triolo et al, 2019), especially since Vineyard C was rain-fed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both temperature and precipitation can have a reducing influence on yield development during extreme events. Finally, temperature and water availability are known to be particularly influential on yield during specific phenological periods (Ojeda et al, 2001;Petrie and Clingeleffer, 2005;Keller et al, 2010;Guilpart et al, 2014;Pagay and Collins, 2017;Triolo et al, 2019). These periods of sensitivity are related to the successive implementation of yield components (Laurent et al, 2021) and their timing and duration is hypothesised to vary depending on the terroir, including vineyard management factors.…”
Section: Introductionmentioning
confidence: 99%
“…The phenylpropanoid pathway is controlled by diverse biotic and abiotic factors, among which, water availability is known to significantly affect the levels and physicochemical properties of grape phenolics. Specifically, a moderate water deficit is reported to positively affect the accumulation of skin anthocyanins (Theodorou et al, 2019) and proanthocyanidins (Cassasa et al, 2015) either indirectly by improving within vine allocation of photosynthates or increasing the skin proportion of (generally smaller) berries (Triolo et al, 2019), or by directly stimulating secondary metabolism by up-regulation of the specific genes of the phenylpropanoid pathway (Castellarin et al, 2007b). In fact, many studies have reported that berry mass per se is unlikely to be the main driver of increased phenolic concentration in grapes and that the cultural practices that induce those small berries are responsible for a large part of the observed changes in berry chemistry (Roby et al, 2004;Mirás-Avalos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between soil and irrigation was never significant for the productive parameters ( Table 5 ). Reductions of berry weight under rain-fed conditions have been already reported [ 55 , 56 , 57 , 58 , 59 , 60 ] and are most likely due to a reduction of cell expansion [ 56 ]. Soil type and irrigation treatment did not affect TSS content, while they had a significant influence on TA ( Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Neither soil nor irrigation influenced the must sugar. However, in the literature, contradictory results regarding the influence of irrigation on yield and must sugar have been obtained depending on vintage, cultivars and rootstocks, time and intensity of water deficit [ 13 , 14 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ], as well as water amounts distributed during the season [ 57 ], in the ripening period, and near harvest.…”
Section: Resultsmentioning
confidence: 99%